2004
DOI: 10.1245/aso.2004.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence and Death After Primary Surgical Treatment of Malignant Phyllodes Tumors

Abstract: Stromal overgrowth in MPT carries a grave prognosis. Close surgical margins and large tumor size, but not type of operation, significantly increased LR. Either WLE with adequate margins or mastectomy is an appropriate treatment for patients with MPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(178 citation statements)
references
References 32 publications
9
162
4
3
Order By: Relevance
“…The commonest sites for distant metastasis are the lungs (66%), bones (28%), and brain (9%) and in rare instances, the liver and heart [7]. Metastasis to axillary lymph nodes occurred in only 2% [8]. Various other malignancies as angiosarcoma, chondrosarcoma, osteosarcoma, liposarcoma, leiomyosarcoma, and rhabdomyosarcoma, are rarely encountered in malignant phyllodes tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonest sites for distant metastasis are the lungs (66%), bones (28%), and brain (9%) and in rare instances, the liver and heart [7]. Metastasis to axillary lymph nodes occurred in only 2% [8]. Various other malignancies as angiosarcoma, chondrosarcoma, osteosarcoma, liposarcoma, leiomyosarcoma, and rhabdomyosarcoma, are rarely encountered in malignant phyllodes tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Since an excision with the required margins is often impossible in giant phyllodes tumors, mastectomy should be reserved for larger tumors and should be considered in recurrent tumors, especially of the malignant histotype [8]. Depending on the size of the breast and the location of the phyllodes tumor, mastectomy may also be required for tumors that are between 5 and 10 cm in diameter [9].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, a more conservative surgical approach is preferred based on the notion that local recurrences (LR) do not appear to be related to the systemic spread of the disease. [23,24] However, studies have reported results contrary to this view too. [15,25] The recent trend towards breast conservation has had a variable impact on the risk of local recurrence (reported as 20-30% for malignant tumors) without an apparent adverse effect on overall survival (OS).…”
Section: Surgerymentioning
confidence: 92%
“…[22] series with mastectomy being performed in some of the cases to achieve negative margin. [24,25,27] Notably, a study by Barth et al in a large review found that the recurrence rate for borderline and malignant PTs remained high even after WLE to the tune of 29 and 35%, respectively. [15] Similar results were also observed by Hassan et al with LR rate after WLE being 0, 36.4, and 40% for benign, borderline, and malignant PTs, respectively.…”
Section: Histological Classificationmentioning
confidence: 99%
“…Benign phyllodes tumor has a 21 % risk of local recurrence, while that of the malignant variety ranges from 20 to 32 %. In patients with malignant phyllodes tumor, the rate of distant metastases ranges from 25 to 40 % [3][4][5][6]. The most frequent sites of distant metastasis include the lungs, bone, heart and liver.…”
mentioning
confidence: 99%